Collaboration Comics in Teaching Practitioner Program - Rizki Taufik Rakhman; Rizky Wardhani; Iwan Gunawan (Nusantara Science and Technology Proceedings, 2023)
Practical teaching is a program initiated by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia so that college graduates are better prepared to enter the world of work. The Fine Arts Education study program responds to the practitioner teaching program in illustration courses. The research entitled, "Gatot Kaca Pusaka Multiverse: Collaborative Comics for Teaching Practitioner Programs" aims to evaluate teaching practitioner programs in illustration courses through outputs in the form of artistic work products resulting from collaboration between students, teaching lecturers and practitioner lecturers. Qualitative method in the learning process by recording all events and obstacles at each meeting for 6 times or 1.5 months. Apart from that, the design thinking method is used when students design the collaborative comic, where the researcher will invite students to carry out the five steps in the form of: Empathize, Define, Ideate, Prototype, and Test/Evaluate. Publications in the form of comics that have an ISBN are the target output in research, in addition to scientific articles in national/international journals and proceedings. The results of the research are expected to become initial recommendations for teaching practitioner programs in the Fine Arts Education study program, Jakarta State University.